1975
DOI: 10.1136/hrt.37.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Premonitory sign of heart block in acute posterior myocardial infarction.

Abstract: The appearance of the QRS complex in leads V3R and V4R was analysed in a series of 94

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Another study in our local population by Saif M et al 15 observed 28.0% RVI in patients with acute IWMI. Barrillon et al 16 highlighted the increased risk of conduction problems in patients with RV involvement, while a study conducted by Zehender et al 17 reported a higher incidence of ventricular fibrillation and sustained ventricular tachycardia in patients with RV involvement as indicated by ECG. Mehta et al 18 conducted a largescale study that compared clinical manifestations and outcomes of patients with acute myocardial infarction based on right ventricular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in our local population by Saif M et al 15 observed 28.0% RVI in patients with acute IWMI. Barrillon et al 16 highlighted the increased risk of conduction problems in patients with RV involvement, while a study conducted by Zehender et al 17 reported a higher incidence of ventricular fibrillation and sustained ventricular tachycardia in patients with RV involvement as indicated by ECG. Mehta et al 18 conducted a largescale study that compared clinical manifestations and outcomes of patients with acute myocardial infarction based on right ventricular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…A study in a dog model [32] demonstrated a marked deterioration in the RV end-diastolic size, systolic pressure, and contraction in cases of RCA ligation with isolated ligation of the right atrial branch. sustained ventricular tachycardia, all leading to higher mortality rates [33], were found more often in patients with RVI [9,[11][12][13]34]. Complete SA or AV blocks leading to bradycardia and loss of atrioventricular synchrony account in part for the ventricular dysfunction [35] and the development of hypotension and shock [36].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of RVI varies from no hemodynamic compromise to cardiogenic shock and multi-organ failure [1,3,7,8,]. Right ventricular involvement in inferior-wall infarction is associated with higher rates of major complications and increased in-hospital-mortality [2,3,7,[9][10][11][12][13][14]. Although the short-term prognosis for RVI is poor, patients who survive the hospitalization show better long-term prognosis compared to patients with shock due to LV failure [15].…”
Section: Introductionmentioning
confidence: 99%
“…Barrillon et al [17] were the first to recognize the significantly higher risk of conduction disorders in patients with RVI. Complete atrioventricular (AV) or sinoatrial blocks occurred in one half of cases in which STE in V4R were present.…”
Section: Discussionmentioning
confidence: 99%